2007
DOI: 10.1128/jb.01651-06
|View full text |Cite
|
Sign up to set email alerts
|

Quinone Reduction by the Na+-Translocating NADH Dehydrogenase Promotes Extracellular Superoxide Production inVibrio cholerae

Abstract: The pathogenicity of Vibrio cholerae is influenced by sodium ions which are actively extruded from the cell by the Na ؉ -translocating NADH:quinone oxidoreductase (Na ؉ -NQR). To study the function of the Na ؉ -NQR in the respiratory chain of V. cholerae, we examined the formation of organic radicals and superoxide in a wild-type strain and a mutant strain lacking the Na ؉ -NQR. Upon reduction with NADH, an organic radical was detected in native membranes by electron paramagnetic resonance spectroscopy which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 37 publications
0
20
2
Order By: Relevance
“…We favor another explanation for the observed stabilization of catecholates by V. cholerae growing in serum-SAPI. Distinct conversion products of NE (eluting at 5.4 min) and of E (eluting at 5.8 min) were detected in the V. cholerae cultures grown for 48 h. Most likely, these compounds are formed by oxidation of NE or E by O 2 or, in a faster reaction, by an extracellular superoxide, O 2 Ϫ , formed by V. cholerae during respiration (42). In the case of E, a possible candidate is leucochrome, which further reacts to adrenochrome (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We favor another explanation for the observed stabilization of catecholates by V. cholerae growing in serum-SAPI. Distinct conversion products of NE (eluting at 5.4 min) and of E (eluting at 5.8 min) were detected in the V. cholerae cultures grown for 48 h. Most likely, these compounds are formed by oxidation of NE or E by O 2 or, in a faster reaction, by an extracellular superoxide, O 2 Ϫ , formed by V. cholerae during respiration (42). In the case of E, a possible candidate is leucochrome, which further reacts to adrenochrome (28).…”
Section: Discussionmentioning
confidence: 99%
“…We propose that compared to bacteria in the cell-free medium, growing bacteria provide a more reducing environment that slows down the oxidative degradation of NE or E. First, O 2 tension is lowered due to the metabolic activity of the bacteria; second, reactive oxygen species (ROS) like superoxide, which accelerate the oxidative degradation of NE or E (28) and which are formed during the initial oxidation step (44), are eliminated by ROS-protective enzymes like the periplasmic superoxide dismutase of V. cholerae (42). To the best of our knowledge, qseC expression levels in bacteria exposed to NE or E during growth have not yet been correlated with the actual concentrations of these signaling compounds in the medium.…”
Section: Discussionmentioning
confidence: 99%
“…V. cholerae operates a redox-driven Na ϩ pump in the NADH:quinone segment of its respiratory chain, but it does not possess a NADH dehydrogenase belonging to the complex I family of enzymes (2). The Na ϩ -translocating NADH:quinone oxidoreductase produced superoxide in vitro (8) and participated in the extracellular formation of superoxide by V. cholerae in vivo (30). We compared the ROS formation activities of membranes from different V. cholerae strains with various amounts of active NQR.…”
Section: Resultsmentioning
confidence: 99%
“…The strong fluorescence of cells suggested that DCF was localized inside the cell, but since V. cholerae is a Gram-negative bacterium, a periplasmic localization of the fluorophore was also considered. If the fluorophore were predominantly accumulated in the periplasm surrounding the cell, formation of DCF fluorescence would reflect extracellular formation of superoxide (30). To address this question, V. cholerae cells loaded with DCFH-DA were treated with lysozyme which results in the formation of spheroplasts due to lysis of the peptidoglycan layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation